PENGELOMPOKAN DATA PELAYANAN KESEHATAN DI KOTA MAKASSAR MENGGUNAKAN WARD’S METHOD - Muthahharah, Isma; Juhari, Agusalim (PATTIMURA UNIVERSITY, 2020)
In health services, the quality of service places patients as the party who consumes and enjoys health services, including those that most determine the quality of health services. The Makassar city health office noted that the people served in 2018 reached 81.77% compared to 2017 which was only 81.71%. The data released by the health department have not shown specifically which districts had very good, pretty good, and poor health services during the Covid-19 pandemic. Therefore, we need a classification method, namely the ward's method. Health services in this study include hospitals, health centers, home care and telemedicine in 15 sub-district locations. Based on the results of the analysis formed 3 clusters, namely cluster 1 with members of the sub-districts of Biringkanaya, Bontoala, Makassar, Manggala, Tallo, Tamalanrea, and Wajo which have pretty good health services. cluster 2 with sub-district members namely Mamajang, Panakkukang, Rappocini, Ujung Pandang, and Sangkarang Islands which have very good health services, cluster 3 with members of Mariso, Tamalate and Ujung Tanah sub-districts which have poor health services.